Embryo Development of Tree Frog Polypedates leucomystax at Campus of State University of Malang - Pearlindah Peralindah; Emy Kusumawati; Dian Ratri Wulandari; Dwi Listyorini (Journal of Tropical Life Science, 2012)
Tree frogs live in natural places which are unpolluted. Regarding their role as an ecological indicator, the decrease of frogs population in a particular habitat indicates the danger of environment quality decrease. Moreover, this condition can harm the frogs themselves. All kinds of frogs breed in aqueous environment such as ponds, marshes, and farming fields. One of the tree frogs, Polypedates leucomystax, which belongs to Familia Rachophoridae, is widely spread in Indonesia. This frog has yellowish brown skin with black spots or six lines extending from head to the posterior tip of body. A breeding couple of the frog produces foam nests on the water or plants around water body, where they will nest their fertilized eggs. This species produces over a hundred embryos in one spawning season. These embryos require appropriate conditions to develop normally in the nature. Frog embryo development may becomes a reference to understand how the frog population survives. This study focused on P. leucomystax with regards to its decrease in number due to the drying up of the environment and a lot lost of trees in Campus of State University of Malang. The development of P. leucomystax embryos in the reproduction foam was observed until it reached a tadpole stage. The result showed that the embryos developed in the foam until they hatched then they move out of the foam into the water under which they would continue their development. Considering that water body is a critical requirement for the development of P. leucomystax embryos, it is our responsibility to make any efforts to conserve not only the trees but also any type of water bodies including ponds, marshes, and farming fields as well. Keywords: embryo development, Polypedates leucomystax, Tree frog conservation